The fiscal impact of immigration in the EU - Christl, Michael,Bélanger, Alain,Conte, Alessandra,Mazza, Jacopo,Narazani, Edlira (European Commission, 2021)
The increasing flows of immigrants in Europe over the last decade has generated a range of considerations in the policy agenda of many receiving countries. One of the main considerations for policy makers and public opinions alike is whether immigrants contribute their
10419/248823
Keywords: Graue Literatur; Migration; Microsimulation; Tax-benefit; system; EUROMOD